A Cross Sectional Study on Correlation of Quantitative C - reactive protein with CD4 Count in Patients of HIV on Art (Academia Journal of Medicine, 2019)
Background: Over the past two decades with the advent of highly active antiretroviral therapy (HAART), there is a substantial increase in the  life span of HIV patients. Hence, the focus has now shifted to managing long-term complications of HIV infection and improving the quality of  life of HIV patients, especially in developed nations. On the other hand, in developing nations, the ever-growing incidence of HIV infection  has placed a huge burden on their frail economy, so there is a growing need for simplifying HIV treatment protocols and for having cheaper  alternatives for monitoring disease activity. Subjects and Methods: The present study was a cross sectional hospital based study for a period  of twelve months from 1st Nov. 2015 to 31st Oct. 2016 at ART center P.B.M. Hospital, Bikaner. 100 HIV+ patients on ART were included in  the study by consecutive sampling technique. Out of 100 patients, 50 were symptomatic and included in study group and remaining 50 were  asymptomatic and taken as controls. Results: 37 (74%) patients in study group had CRP levels >6 mg/lit (normal level 20 mg/lit. While in control group, 44 subjects (88%) had CRP level 6mg/lit. None of control subjects had CRP level >20 mg/lit. The CRP levels and CD4 count were  negatively correlated in study group and this was observed to be statistically significant (p=0.04) whereas in control group, the CRP levels and  CD4 counts were found to be very weakly positively correlated and this correlation was observed to be statistically insignificant. Conclusion:  There was statistical significant difference between CRP range and levels in both the groups. Also statistical significant difference between  CD4 count range in both the groups. In our study, 38% of the study group patients had CRP >20 mg/l whereas 88% of the control subjects had  CRP of
Keywords: HIV; CRP; CD 4; HAART